Corporal Punishment as an Educational Practice for Burundian Children’s Maladaptive Behavior: The Assessment of the Disposition of Children Education Stakeholders - Ladislas, Gahungu (European Scientific Journal, ESJ, 2023)
Our study aims to investigate the factors that produce and sustain the use of corporal punishment in education in Burundi. To collect data, we used a life story approach with semi-structured interviews and direct and indirect observation of educational actors. Analysis of the empirical corpus of 50 educational actors enabled us to highlight the social and educational experiences of our interviewees drawn from their childhood. Religious beliefs, the personality of the educators and psychic tensions linked to the general context are the main reasons for the use of corporal punishment. The majority of our interviewees, including teachers, support the use of corporal punishment, provided it does not exceed certain limits. Sensitivity to the effects of corporal punishment on children is generally low. It changes and rises to physical and economic effects, which arise when corporal punishment results in serious bodily harm, requiring prolonged hospitalization of the victim. For our respondents, not punishing children would be synonymous with cowardice, a violation of biblical scripture, with a high risk of exposing children to more dangerous consequences. Finally, to prevent and reduce the early onset of maladaptive behavior in children, the introduction of positive parenting programs is indispensable in Burundian education.